Ethylene and Metal Stress: Small Molecule, Big Impact - Keunen, Els; Schellingen, Kerim; Vangronsveld, Jaco; Cuypers, Ann (Frontiers in Plant Science, 2016)
The phytohormone ethylene is known to mediate a diverse array of signaling processes during abiotic stress in plants. Whereas many reports have demonstrated enhanced ethylene production in metal-exposed plants, the underlying molecular mechanisms are only recently investigated. Increasing evidence supports a role for ethylene in the regulation of plant metal stress responses. Moreover, crosstalk appears to exist between ethylene and the cellular redox balance, nutrients and other phytohormones. This review highlights our current understanding of the key role ethylene plays during responses to metal exposure. Moreover, particular attention is paid to the integration of ethylene within the broad network of plant responses to metal stress.